Sir C.P. remembered : to Thatha with love : a granddaughter's reminiscences - Shakunthala Jagannathan (Vakils, Feffer & Simons Ltd., 1999)
On the life and works of Chetpat Pattabhirama Ramaswami Aiyar, 1879-1966, legal advisor to the ruler of Travancore State.